2019
DOI: 10.1177/0894439319851503
|View full text |Cite
|
Sign up to set email alerts
|

Do Distractions During Web Survey Completion Affect Data Quality? Findings From a Laboratory Experiment

Abstract: Web survey respondents are frequently distracted during survey completion, which potentially affects the quality of data they provide. This article reports on results from a laboratory experiment examining how distractions during web survey completion influence data quality. Participants were randomly assigned to experimental groups using a 2 (device type) × 3 (form of distraction) between-subject factorial design. They were asked to complete a web questionnaire on either a PC or a tablet and were allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
(59 reference statements)
2
18
0
Order By: Relevance
“…Therefore, research that uses further response quality indicators is required. Fifth, it would be desirable if future studies employ more refined situational factors, such as noisy or quiet environments (see Wenz, 2019), to explain total acceleration of smartphones during web survey completion. Finally, we only focused on two motion conditions (standing or walking).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, research that uses further response quality indicators is required. Fifth, it would be desirable if future studies employ more refined situational factors, such as noisy or quiet environments (see Wenz, 2019), to explain total acceleration of smartphones during web survey completion. Finally, we only focused on two motion conditions (standing or walking).…”
Section: Discussionmentioning
confidence: 99%
“…While some earlier studies have confirmed indications of some of these effects, as summarised in, e.g., Couper et al (2017) and de Leeuw (2018), some recent experimental studies have somewhat surprisingly found small or no device effects, generally concluding that smartphone responses are of comparable quality to computer responses (e.g. Antoun et al 2017;Lugtig and Toepoel 2016;Schlosser and Mays 2018;Tourangeau et al 2018;Wenz 2019). The only two studies in the SP literature in environmental and resource economics comparing devices that we are aware of have generally come to the same conclusion.…”
Section: Introductionmentioning
confidence: 91%
“…Consequently, smartphone respondents are frequently surrounded by third parties during survey participation (Toninelli & Revilla, 2016b), which might have a negative impact on response behavior because respondents can get distracted due to their environment. Lynn and Kaminska (2012) distinguish three types of distractions during survey participation: (1) distractions that demand aural attention, such as music playing in the background (see also Wenz, 2019), (2) distractions that demand visual attention, such as looking after children, and (3) multitasking, such as having a conversation. Indeed, Toninelli and Revilla (2016a) show that smartphone respondents report more distractions and/or multitasking behavior, such as watching TV and talking with other people, than PC respondents.…”
Section: Introductionmentioning
confidence: 99%
“…However, one problem associated with these findings on distractions and multitasking is that they are based on self-reports, implying that respondents must admit that they might not pay constant attention. Thus, self-reports on distractions and multitasking are subject to social desirability bias and recall error, which might cause imprecise measures (Wenz, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation